2018
DOI: 10.24088/ijbea-2018-36002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Using Total Quality Management on the Financial Performance of Companies Listed on the Palestine Exchange

Abstract: Value chains have become more complex because of ongoing globalization and the cost pressure in production and development. As part of these trends, companies must make far-reaching decisions about vertical integration and early-stage supplier integration during product development. Estimations show that suppliers, especially in the automotive industry, already generate 70% to 90% of the value-added. Suppliers play a decisive role in how the product is developed and manufactured, why a functioning supplier int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Prior researchers have argued that these tangibles have a significant influence on organizational overall financial performance. Alatrash (2018) reported that tangible goods, a comfortable workplace environment, convenience in using corporate equipment and appropriate training of new technological equipment have a positive influence on corporate financial performance. Furthermore, Sila (2018) stated that a positive relationship exists between workplace environment, managerial employees, tangible goods, level of comfortableness, and company performance in both financial and non-financial terms.…”
Section: Tqm and Financial Performancementioning
confidence: 99%
“…Prior researchers have argued that these tangibles have a significant influence on organizational overall financial performance. Alatrash (2018) reported that tangible goods, a comfortable workplace environment, convenience in using corporate equipment and appropriate training of new technological equipment have a positive influence on corporate financial performance. Furthermore, Sila (2018) stated that a positive relationship exists between workplace environment, managerial employees, tangible goods, level of comfortableness, and company performance in both financial and non-financial terms.…”
Section: Tqm and Financial Performancementioning
confidence: 99%
“…It can be argued that rapid environmental changes would influence the deterioration patterns found in struggling organizations. Environmental change that is difficult to predict is more challenging in terms of organizational responses (McCarthy, Ian P and Lawrence, Thomas B and Wixted, Brian and Gordon, Brian R, 2010;Shahri & Sarvestani, 2020;Alatrash, 2018). When facing rapid change, there is less time for decision-making, resource allocations, and other moves that enable firms to respond effectively to the environment.…”
Section: Theoretical Background and Frameworkmentioning
confidence: 99%